2003
DOI: 10.1175/1525-7541(2003)004<0673:sitseb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in the Surface Energy Balance of Tundra in the Lower Mackenzie River Basin

Abstract: This study details seasonal characteristics in the annual surface energy balance of upland and lowland tundra during the 1998-99 water year (Y2). It contrasts the results with the 1997-98 water year (Y1) and relates the findings to the climatic normals for the lower Mackenzie River basin region. Both years were much warmer than the long-term average, with Y1 being both warmer and wetter than Y2. Six seasons are defined as early winter, midwinter, late winter, spring, summer, and fall. The most rapid changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Thus, lakes and wetlands significantly changed the partitioning of precipitation to ET and total runoff within the study domain. Similar results were identified by Bowling and Lettenmaier (2010) and Rouse et al (2008) for modeling and observations based studies, respectively.…”
Section: Regional Hydroclimatologysupporting
confidence: 86%
See 4 more Smart Citations
“…Thus, lakes and wetlands significantly changed the partitioning of precipitation to ET and total runoff within the study domain. Similar results were identified by Bowling and Lettenmaier (2010) and Rouse et al (2008) for modeling and observations based studies, respectively.…”
Section: Regional Hydroclimatologysupporting
confidence: 86%
“…As ET increased, annual average total runoff decreased from 35%-31% with the inclusion of lakes and wetlands. Rouse et al (2008) reported similar characteristics (i.e., more ET and less total runoff) for lake/wetland dominated regions in the central Mackenzie River basin, relative to upland areas. During the summer, the water balance deficit in the lake-dominated region was increased twofold during the dry years (Rouse et al 2008) compared to average conditions.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations